Influence of Thermally Oxidized Vegetable Oil and Animal Fats on Growth Performance, Nutrient Digestibility, Carcass Parameters and Meat Quality of Broilers - Kamran,J (2020)
ABSTRACT The current study was planned to investigate the influence of soy oil, oxidized soy oil, poultry oil single refined and poultry oil double refined on the performance of broilers chicken. A total of two hundred and forty, day-old broiler chicks were divided into 4 treatments in such a way that each treatment had six replicates and each replicate had ten chicks. The experimental treatments were separated with the usage of single refined poultry oil, double refined poultry oil, oxidized soy oil and soy oil in the diet of broilers. In both starter and overall periods average body weight was higher (p<0.05) for birds which were on a basal diet containing soy oil as compared to other diets. Similarly, feed intake was higher (p<0.05) for birds which were on a basal diet containing soy oil in the starter phase. In the overall phase, average body weight was less in oxidized oil as compared to other dietary treatments (p<0.05). Similarly, birds showed poor feed conversion ratio in the basal diet that contained oxidized oil (p<0.05) in the overall phase of the experiment. The birds showed better digestibility (p<0.05) for crude fat on a basal diet containing vegetable oil and double refined poultry oil as compared to other diets. Results showed no effects of experimental treatments on the meat quality and carcass parameters (p>0.05). Therefore, it can be concluded that poultry single refined and double refined oil could be a possible substitute for fresh soy oil for better performance as compared to oxidized soy oil.